BANK MANAGEMENT SYATEM - C. Geetha, Srikanth, .Sai Kumar (International Journal of Modern Agriculture, 2020)
Bank Management System project is written in Python. The project file contains a python script (main.py) and a database file. This is a simple console based system which is very easy to understand and use. Talking about the system, it contains all the basic functions which include creating a new account, view account holders record, withdraws and deposit amount, balance inquiry, closing an account and edit account details. It is too easy to use, he/she can check the total bank account records easily.